Ectopic Pancreas Presenting as Periampullary Tumor with Obstructive Jaundice and Pruritus Is a Rare Diagnostic and Therapeutic Dilemma. A Case Report - Rao, Ram Nawal; Kamlesh, Yadav; Pallav, Gupta; Singla, Nidhi (JOP. Journal of the Pancreas, 2011)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Context Ectopic pancreatic rest is an uncommon condition resulting in diverse clinical and pathological presentation. It results from altered development of two primitive pancreatic buds that fuse to form the uncinate-head and body-tail of normal gland. Ectopic pancreas is an anomaly where an ectopic rest develops at a place away from the normal site. Case report We describe a 48-year-old male patient who presented with progressive jaundice and pruritus. He was established to have a periampullary mass highly suggestive of malignancy, for which he undergo pancreaticoduodenectomy. However, histology showed ectopic pancreatic tissue in the periampullary region. Conclusion This case highlights importance of preoperative histological diagnosis of periampullary tumors to avoid morbid surgical procedure in the form pancreaticoduodenectomy. Ectopic pancreas should include differential diagnosis of periampullary tumors.